(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to shed light on the Just-In-Time (JIT) production system. To achieve the objectives of the study, the researchers conducted a field investigation involving four companies specialized in the food industry: Al-Naseem Food Industries (Misurata), South Mediterranean for Food Development – Al-Wafaa Tuna Factory (Al-Khums), Al-Jayd Food Industries (Misurata), and Lebda Food Industries (Al-Khums). A total of 100 questionnaires were distributed to employees across various departments, of which 62 were returned, representing a response rate of 62%. Several statistical tools were employed, including Cronbach’s Alpha to assess reliability and Cohen’s d to measure effect size. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS). The study revealed several key findings. Among the most significant indicators of cost reduction were the application of modern material handling methods and the enhancement of production efficiency. Furthermore, factory layout design and operational efficiency were identified as major factors contributing to the reduction of production time. Additionally, attracting highly qualified personnel and selecting high-quality raw materials were found to be key factors in reducing defect rates. The study recommended the broader implementation of modern handling technologies, improving efficiency across production stages, and investing in quality and human resources. It also emphasized the need for adopting smart monitoring systems to achieve efficient production and lower costs.